Analisa Dan Perancangan Aplikasi Persediaan Obat Studi Kasus: Klinik Umum - Dede Firmansyah Saefudin (Paradigma, 2018)
Abstract— The inventory system in every government or private agency, especially in the health sector is very vital, managing a stock of goods carefully and scheduled to give an impact on the performance effectiveness of each company and to improve for the better  service consumers. To see the extent of the clinical supply system at the clinic and its level of performance, and whether the drug storage system used so far is effective and efficient for optimal benefits. From the research conducted, the authors found a weakness in the system used so far is considered less effective and efficient because it takes a long time to get information on drug supply data (manual system), either expired or reduced. the design of a drug supply information system is expected to assist the user in this part of the inventory to find out the stock data information or expiration on the drug supply effectively and detail up to the inventory reports and drug information per category. Keywords: design, information system, drug supply, clinic.